Analysis of the mechanism underlying the effects of cyclophosphamide against triple-negative breast cancer by an integrative bioinformatics approach - Maojing Wang; Wenwen Li; Ding Li; Zhiwu Han (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2021)
Patients with Triple-Negative Breast Cancer (TNBC), a highly heterogeneous and invasive subtype of breast cancer, do not benefit from hormonal therapy or trastuzumab; therefore, chemotherapy is considered the only option. We explored the effect of the chemotherapeutic drug cyclophosphamide (Cytoxan; Cy) on TNBC by an integrated bioinformatics approach. Methods: Pharm Mapper, Gene Cards, and Swiss Target Prediction were used to identify potential targets of Cy. Differentially expressed genes (DEGs) in TNBC were screened out from four GEO datasets. Common genes were further evaluated by a protein-protein interaction network analysis, core gene identification, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, docking assays, and survival and immune cell infiltration analyses. Results: We collected information on 1638 drug targets and 494 DEGs in TNBC, including 267 up-regulated and 227 down-regulated genes. In total, 68 overlapping genes were identified as common targets. Ten core genes were identified in network analysis; GO and KEGG analyses revealed enrichment for DNA damage and many signaling pathways. Four core gene targets were verified by molecular docking. Kaplan-Meier analysis revealed that two core genes were significantly related to an adverse overall survival; furthermore, immune infiltration analysis suggested that Cy affects the microenvironment. Conclusions: Our integrative bioinformatics approach revealed that the anti-TNBC effect of Cy was mediated by DNA damage-related genes and many pathways. These findings provide a basis for further functional studies aimed at improving outcomes in TNBC.